Defectos refractivos y su incidencia en el desempeño profesional de docentes de la Unidad Educativa Fluminense Parroquia Patricia Pilar, Provincia de Los Ríos, octubre 2018 – abril 2019 - Mendoza Mendoza, Viamna Yamilex (2019)
Introduction: The work responds to the need to investigate the influence of low visual acuity and its direct and indirect relationship with professional performance since this has a double impact on the one hand affects the teacher in his intellectual capacity which also indirectly affects the student in terms of their knowledge which affects the achievement of their academic goals. Objective: To design visual health training for teachers with refractive errors in their professional performance in the Educational Unit "Fluminense" Patricia Pilar Parish, Province of Los Ríos, October 2018 - April 2019. Methodology: the deductive and the inductive method were applied, the modality that was used is a field of investigative work and with bibliographic contents, it is descriptive, diagnostic and explanatory. With the use of direct observation techniques, direct evaluation and survey, the necessary information was collected. Results: The respective visual exams were made to each teacher detecting that: 12 teachers have presbyopia corresponding to 32%, 11 teachers have nearsightedness corresponding to 29%, 8 docs hyperopia corresponding to 21% and 7 teachers astigmatism corresponding to 18 %, of the 38 teachers rated at 74%, these refractive errors affect their professional performance and 26% do not affect them. Conclusions: The study shows the direct and indirect influence of the use of the computer in low visuality in the professionals which also has a direct effect of the intellectual productivity of the teacher, of the representative group of the sample it is shown that 74% of the professionals attend to a visual health professional. Ignorance about visual health and prolonged use of computers or cell phones, which leads to many damage to vision.